Justicia alternativa y construcción del Estado desde lo local en el contexto rural colombiano - Iván Camilo Vargas-Castro (Revista Iberoamericana de Estudios de Desarrollo)
In this research, it is aimed to expose and analyze some alternative justice and conflict resolution practices developed by peasant communities in the Catatumbo region (North of Santander, Colombia), in a context where the presence of the armed conflict and the implementation of the peace agreement allow a debate on the legitimacy and legality of these alternative practices of justice and citizen coexistence. In this research, it is hypothesized that the strengthening of alternative justice practices, especially those developed by peasant communities, contribute to the construction of the State from the local level. Through the analysis of the current regulations, the theoretical aspects and the phenomenological description of community practices, the dilemmas faced by understandings of justice, conflict resolution methods, and peacebuilding practices are exposed in a context where the armed conflict has not yet been overcome.